Tourist Legal Protection Through Manado’s Regional Regulation to Increase Tourism Level in Manado - Novritsar Hasintongan Pakpahan (Journal of International Conference Proceedings (JICP), 2019)
The low level of tourism in Indonesia especially in Manado, North Sulawesi is due to a lot of factors such as lack of tourism regulation. Tourism regulation regulates legal formality and substance. This study focuses on the local tourism regulation and its application to tourism. It is found that the enactment of the regulation is not followed by regular assessment which caused the lack of safety for tourist and unfair treatment towards international tourist. Although Perda No. 2/2015 and Perwali 15/2016 has regulated the conduct of tourism business and protection, it still needs better enforcement regarding tourist protection through clearer implementation instruction, such as an independent body to foresee the legal obedience of the holder of tourism business license.